2016
DOI: 10.1210/jc.2016-2254
|View full text |Cite
|
Sign up to set email alerts
|

Partial Loss of Function of the GHRH Receptor Leads to Mild Growth Hormone Deficiency

Abstract: We report the first coexistence of two novel compound homozygous GHRHR variants in two unrelated pedigrees associated with a partial loss of function. Surprisingly, the patients have a relatively mild IGHD phenotype. Analysis revealed that the pP79L mutation is associated with the compromise in function, with the residual partial activity explaining the mild phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Means are shown ± standard deviation the variant, Gregory et al (2016) showed in a recent report that the p.(R4Q) variant does not affect the response of HEK293 cells to GHRH. Third and most important, as shown here, the cAMPmediated transcriptional activity of the receptor carrying those variants was found to be similar to that of the normal GHRHR.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Means are shown ± standard deviation the variant, Gregory et al (2016) showed in a recent report that the p.(R4Q) variant does not affect the response of HEK293 cells to GHRH. Third and most important, as shown here, the cAMPmediated transcriptional activity of the receptor carrying those variants was found to be similar to that of the normal GHRHR.…”
Section: Discussionmentioning
confidence: 96%
“…Under the hypothesis of a dominant transmission of the disease phenotype suggested for those variants, this would mean that 1.8% and 1% of subjects from these control populations may have IGHD, an estimate that largely overcomes the prevalence of the disease (1/10,000–1/4,000). In addition, as for the p.(R4W) the variant that involves the same residue as the p.(R4Q) the variant, Gregory et al () showed in a recent report that the p.(R4Q) variant does not affect the response of HEK293 cells to GHRH. Third and most important, as shown here, the cAMP‐mediated transcriptional activity of the receptor carrying those variants was found to be similar to that of the normal GHRHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, several patients exhibiting HPE anomalies present This functional study shows how haploinsufficiency of both the SHH and NOTCH signalling pathways may contribute to not only to HPE but also to congenital hypopituitarism. This study has clinical implications, as many cases are not yet fully explained by genetic testing (12,69).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Null-type GHRH-R mutations lead to unmeasurable IGF-1 levels and are accompanied by mild ocular disorders ( 14 ). Missense GHRH-R variants -such as p.G369V or p.T257A- result in partial loss of receptor function due to defective ligand binding and milder phenotypes, occasionally accompanied by hypoglycemia ( 15 ). Splice site mutations of untranslated and coding regions have been reported to lead to gross indels with loss of 5’ regulatory/exon 1 region, leading to fully impaired GHRH-R expression ( 12 ).…”
Section: Discussionmentioning
confidence: 99%